Key Factors for Mitigating Contractor’s Claim on Loss and Expense Due to the Extension of Time in Public Projects: the Causes and Mitigation Measures - Hidayah Yahya, Nor; Fadhil Mohammad, Mohammad; Musa, Marina (International Journal of Engineering and Technology, 2018)
Claim on loss and expense is quite a common occurrence and tends to pile up during a construction project. Nonetheless, it can be mitigated in several ways. This paper aims to show that the causes of the claims is due to the EOT with reference to (PWD) projects in Malaysia on the critical issues and challenges faced by the clients in mitigating contractor’s loss & expense claims. Data were collected through questionnaires distributed among professionals in PWD and private sectors. Recommendations on mitigating contractor’s claims on loss and expense due to EOT are made based on the analysed data. The findings show that factors which can mitigate claim on loss and expense can be categorized into three distinctive groups. All the lessons learnt and solutions from this study could be used in the mitigation of contractor’s claims in future public projects.